SYSTEMATIC REVIEW OF THE INFLUENCE OF TALENT MANAGEMENT, CAREER DEVELOPMENT OPPORTUNITIES, AND POSITIVE WORK ENVIRONMENT ON ORGANIZATIONAL COMMITMENT THROUGH JOB SATISFACTION - Witjaksono Adi Pangestu; Budi Eko Soetjipto; Ludi Wisnu Wardhana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This article presents a systematic literature review (SLR) to analyze the relationship between talent management, career development opportunities, and a positive work environment on organizational commitment, with job satisfaction as a mediating variable. The study was conducted by selecting articles from reputable journals in the Scopus database (Q1–Q4) published between 2019 and 2024. The synthesis of results indicates that strategic talent management, inclusive career systems, and a supportive work environment contribute significantly to strengthening employees' affective loyalty. These findings confirm that job satisfaction is not merely an end result but serves as a key mediator bridging the influence of organizational stimuli on employee commitment. The developed conceptual model expands the application of Herzberg’s Two-Factor Theory and Social Exchange Theory within an evidence-based integrative framework. This study offers theoretical and practical contributions to the development of adaptive, sustainable, and well-being-oriented human resource management policies.